EVALUATE THE IMPACT OF AVAILABILITY PROBLEMS DEEP RESERVOIR WATER SUPPORTS CLEAN WATER QUALITY IN EAST TANJUNGPINANG DISTRICT - Risnawati; Yuanita FD Sidabutar; Raflis Tanjung; Alpano Priyandes (Jurnal Potensi, 2025)
Clean water is a basic need for the survival of humans and other living creatures. In East Tanjungpinang District, Tanjungpinang City, reservoirs are the main source of clean water for the community. As the population increases, the need for clean water also increases and the problem of clean water is significant regarding the availability of reservoir water to support clean water quality in East Tanjungpinang sub-district, Tanjungpinang city. To meet the need for clean water, the main source of which is reservoir water, serious attention is needed from the government, related sectors and the community. Reservoirs are the main source to support clean water quality. Therefore, an in-depth evaluation of the impact of the problem of reservoir water availability in supporting clean water quality in East Tanjungpinang District, Tanjungpinang City is needed, such as a decrease in reservoir water discharge which causes a reduction in clean water reserves, increased pollution due to waste. around the reservoir and sedimentation occurs at the bottom of the reservoir, causing shallowing of the reservoir and reducing the volume and quality of the water. It is hoped that this evaluation can evaluate the impact of reservoir water availability problems in supporting clean water quality in East Tanjungpinang subdistrict and become valuable input for the government, related institutions and the community in formulating policies and strategies for sustainable clean water management in East Tanjungpinang subdistrict, Tanjungpinang city.In this way, the availability of quality and sustainable clean water can be guaranteed, the quality of regional facilities can be improved, and community welfare can be realized